Factors influencing farmers' knowledge about sustainable groundwater management. (2nd May 2019) - Bakhshi, Azadeh; Cecchini, Lucio; Pour, Bahman Khosravi; Ghanian, Mansour; Santucci, Fabio Maria
This paper analyses the influence of socio-economic and structural factors on the knowledge about sustainable groundwater management (SGWM) among farmers in Iran. 189 wheat producers have been interviewed during summer 2017 in the South Khorasan province. The dependent variable (TK, total knowledge) has been constructed through the answers to 18 questions, defined as pk, partial knowledge . The model includes 12 independent variables, which affect TK, and cover both socio-economic and structural aspects, like age, education, income, knowledge about drought, relationship with the local advisory service, water rights, irrigation method, area with wheat, wheat total production, and fragmentation. The results show that there is a correlation, sometimes positive and sometimes negative, between all independent variables and SGWM. Participation in extension meetings, total wheat production, and family income show the strongest positive correlations. A multiple linear regression has been then applied to estimate the influence of the variables on the farmers' total knowledge regarding SGWM. The results show that 45.0% of the total knowledge variance is determined by the independent variables used in the model.